(untitled) (Colombia Medica, 1987)
An exploratory investigation in the Neonatal Intensive Care Unit of the Hospital Universitario del Valle, Cali, Colombia, was carried out to evaluate the effects of adding transfusions of cryoprecipitate as a source of fibronectin to the standard therapy of neonatal sepsis a disease which produces high degrees of morbidity and mortality. Children receiving cryoprecipitate had less mortality, and their recuperation was shorter.